SAM II aerosol profile measurements, Poker Flat, Alaska; July 16-19, 1979 - Mccormick, M. P.; Chu, W. P.; Mcmaster, L. R.; Grams, G. W.; Herman, B. M.; Pepin, T. J.; Russell, P. B.; Swissler, T. J. (1981)
SAM II satellite measurements during the July 1979 Poker Flat mission, yielded an aerosol extinction coefficient of 0.0004/km at 1.0 micron wavelength, in the region of the stratospheric aerosol mixing ratio peak (12-16 km). The stratospheric aerosol optical depth for these data, calculated from the tropopause through 30 km, is approximately 0.001. These results are consistent with the average 1979 summertime values found throughout the Arctic.